2013
DOI: 10.1155/2013/262386
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Brief Daily Resistance Training on Occupational Neck/Shoulder Muscle Activity in Office Workers with Chronic Pain: Randomized Controlled Trial

Abstract: Purpose. This study investigates the acute and longitudinal effects of resistance training on occupational muscle activity in office workers with chronic pain. Methods. 30 female office workers with chronic neck and shoulder pain participated for 10 weeks in high-intensity elastic resistance training for 2 minutes per day (n = 15) or in control receiving weekly email-based information on general health (n = 15). Electromyography (EMG) from the splenius and upper trapezius was recorded during a normal workday. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 59 publications
(67 reference statements)
0
36
0
2
Order By: Relevance
“…To identify workers and work units at high risk of physical impairments, we classified the WAI score according to extant conventions into "poor" (7-27), "moderate" (28)(29)(30)(31)(32)(33)(34)(35)(36), "good (37-43) and "excellent" (44-49) work ability (29). The fact that the baseline average WAI score for our participants was categorized as "good", might at a first glance seem as a paradox since the inclusion criteria included both chronic pain and work disability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To identify workers and work units at high risk of physical impairments, we classified the WAI score according to extant conventions into "poor" (7-27), "moderate" (28)(29)(30)(31)(32)(33)(34)(35)(36), "good (37-43) and "excellent" (44-49) work ability (29). The fact that the baseline average WAI score for our participants was categorized as "good", might at a first glance seem as a paradox since the inclusion criteria included both chronic pain and work disability.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the imbalance between individual physical capacity and physical work demands potentially would be reduced, possibly explaining the observed difference in demands of the job (item 2) between the two groups. Although we did not measure relative exposure during work, a recent study using electromyography has shown lower relative exposure of the neck muscles among office workers during the working day following 10 weeks of strength training (35).…”
Section: Sundstrup Et Almentioning
confidence: 99%
“…14 Lidegaard et al investigated the acute and longitudinal effects of resistance training on occupational muscle activity in office workers with chronic neck-shoulder pain. 15 Acute response to a single session of resistance training appeared to generate an unfavorable muscle activity pattern. 15 Only the changes following 10 weeks of resistance training were beneficial in terms of longer and more frequent periods of complete muscular relaxation and reduced pain.…”
Section: Noninvasive Treatmentmentioning
confidence: 99%
“…15 Acute response to a single session of resistance training appeared to generate an unfavorable muscle activity pattern. 15 Only the changes following 10 weeks of resistance training were beneficial in terms of longer and more frequent periods of complete muscular relaxation and reduced pain. 15 …”
Section: Noninvasive Treatmentmentioning
confidence: 99%
See 1 more Smart Citation